Effectiveness of Combining Compensatory Cognitive Training and Vocational Intervention vs. Treatment as Usual on Return to Work Following Mild-to-Moderate Traumatic Brain Injury: Interim Analysis at 3 and 6 Month Follow-Up - Howe, Emilie Isager; Fure, Silje C. R.; Løvstad, Marianne; Enehaug, Heidi; Sagstad, Kjersti; Hellstrøm, Torgeir; Brunborg, Cathrine; Røe, Cecilie; Nordenmark, Tonje Haug; Søberg, Helene L.; Twamley, Elizabeth; Lu, Juan; et al. (Frontiers in Neurology, 2020)
Aims: Knowledge regarding the most effective return to work approaches after traumatic brain injury (TBI) is lacking. This trial aimed to compare the effectiveness of a combined cognitive and vocational intervention to treatment as usual (TAU) on return to work and work stability after TBI. Methods: We performed a parallel-group randomized controlled trial at a TBI outpatient clinic at Oslo University Hospital, Norway. Patients with a history of mild-to-moderate TBI (n = 116) aged 18-60 were randomized (1:1) by an independent investigator to receive group-based compensatory cognitive training (CCT) and supported employment (SE) (n = 60) or TAU consisting of individualized multidisciplinary treatment (n = 56). Participants were enrolled 2-3 months post-injury. The nature of the intervention prevented blinding of patients and therapists, however, outcome assessors were blinded to group allocation. The primary outcome measure was return to work (RTW) at 3 and 6 months following study inclusion. Secondary outcomes were work percentage, stability, and productivity. The present study provides results from an interim analysis from the first two planned follow ups, while subsequent publications will present results up to 12 months following study inclusion. Results: Mixed effects models showed no between-group differences in the RTW proportion, work percentage, and hours worked between CCT-SE and TAU from baseline to 6 months. A significantly higher proportion of participants in CCT-SE had returned to work at 3 months when adjusting for baseline differences. The majority of participants who were employed at 3- and 6-months were stably employed. There was a statistically significant within-group improvement on RTW proportion, hours worked and work percentage in both groups. Conclusion: The results revealed no difference between CCT-SE and TAU on work-related outcomes from baseline to 6 months. However, there was a higher RTW proportion in the CCT-SE group compared to TAU at 3 months. Future publications will assess the effectiveness of CCT-SE versus TAU up to 12 months. Clinical trial registration: US National Institutes of Health (ClinicalTrials.gov) #NCT03092713.